Ocena zapotrzebowania na finansowe środki obrotowe przedsiębiorstwa (analiza przypadku) - Prus, Janusz (Valuation of Needs for Liquid Assets of a Company (Case Study), 2006)
Financial requirements of a particular enterprise are an object of consideration which is essential to keep a proper rhythm of production. The enterprise's products are seasonal, with several week's period of sale, while their production is kept for the whole year. The estimation of requirements results in analysis of the period of production and sale. The analysis is based on production, sale, magazine stock and on average course of enterprise's production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 494-505